2009
DOI: 10.1007/s10571-009-9400-8
|View full text |Cite
|
Sign up to set email alerts
|

Duck Pancreatic Acinar Cell as a Unique Model for Independent Cholinergic Stimulation–Secretion Coupling

Abstract: This paper investigated the role of acetylcholine (ACh) in physiological regulation of amylase secretion in avian exocrine pancreas. In the isolated duck pancreatic acini, ACh dose dependently stimulated amylase secretion, with a maximal effective concentration at 10 muM. The cAMP-mobilizing compounds forskolin, vasoactive intestinal peptide (VIP)/pituitary adenylate cyclase activating peptide (PACAP) receptor (VPAC) agonists PACAP-38 and PACAP-27 had no effect on the dose-response curve. ACh dose dependently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
4
1
Order By: Relevance
“…The cells in the lumen of acini were observed simple flattened to low cuboidal cells which represent the starting of intercalated ducts,the interlobular ducts of pancreas in bulbul lined by simple cuboidal epithelia which changed to the columnar in main ducts,our results showed no difference with those of (16) in red common quail (Coturnix coturnix) but differ with him when observed the interlobular ducts lined by simple columnar epithelium,also our results not similar with (17) in duck whom noted the main ducts lined by simple to stratified columnar epithelium.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The cells in the lumen of acini were observed simple flattened to low cuboidal cells which represent the starting of intercalated ducts,the interlobular ducts of pancreas in bulbul lined by simple cuboidal epithelia which changed to the columnar in main ducts,our results showed no difference with those of (16) in red common quail (Coturnix coturnix) but differ with him when observed the interlobular ducts lined by simple columnar epithelium,also our results not similar with (17) in duck whom noted the main ducts lined by simple to stratified columnar epithelium.…”
Section: Discussioncontrasting
confidence: 76%
“…The ductal system of avian pancreas composed of intercalated, intralobular, interlobular duct and main excretory duct (pancreatic ducts), the epithelium which lined the ducts varied from simple cuboidal in intercalated and intralobular duct to tall columnar in interlobular duct, this information was noted by (16) in common Quail (coturnix coturnix ),while in early hatched goose (Anser anser) and duck the main excretory ducts were lined by simple to stratified columnar epithelium and these ducts have inner longitudinal and outer circular muscle layers surrounded externally by connective tissue (3,17).…”
Section: Introductionmentioning
confidence: 96%
“…For instance, in amphibians, it has been reported that noradrenaline inhibits mucous secretion from the stomach of amphibians in vitro (Keogh et al, 1997) and that acetylcholine stimulates intestinal mucus secretion in the frog (Slaughter and Aiello, 1982). In birds, pancreatic secretion is stimulated by acetylcholine (Meacham and Johnson, 2003;Murai et al, 2000;Wang et al, 2009) and inhibited by adrenaline (Salido et al, 1985). Similarly, in fish, pancreatic secretion is enhanced by cholinergic agents and inhibited by adrenergic drugs (Milgram et al, 1991).…”
Section: Central Regulation Of Gut Functionsmentioning
confidence: 99%
“…Oscillatory increases in cytosolic calcium in different cell types including mast cells ensure that multiple and specific signals are encoded. Calcium oscillations could be induced by physiological concentrations of hormones and neurotransmitters, [1][2][3] bacterial cytotoxin or IgE, 4,5 but also by ultraviolet A irradiation (UVA, 320-400 nm). 6 Of the solar UV radiation, only UVA and UVB (290-320 nm) can reach the surface of the earth, of which about 95% is UVA.…”
Section: Introductionmentioning
confidence: 99%